PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR PERIODE 2017-2020 - Dheandra Laurensha; Rosalia Nansih Widhiastuti (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2022)
This study aims to determine the effect of financial ratios, namely, Current Ratio, Debt Equity Ratio, Return On Assets, and Growth Assets on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The method used in this research is panel data regression analysis with software tools Eviews 12. The sampling technique uses purposive sampling with a total sample of 27 manufacturing companies. The results show that CR, DER, ROA, and GA have a simultaneous effect on dividend policy. Partially ROA has a positive effect on dividend policy, while CR, DER, and GA have no significant effect on dividend policy